PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP MANAJEMEN LABA DENGAN LEVERAGE DAN GROWTH SEBAGAI VARIABEL CONTROL PADA INDUSTRI FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Marissa Putriana; Susi Artati; Venny Junica Utami (J-MAS (Jurnal Manajemen dan Sains), 2018)
This research aimed to examine the influence of Corporate Social Responsibility on earnings management. The population in this research is the pharmaceutical company on the Indonesia stock exchange. Samples are selected using a purposive sampling method. The data used in this research is 6 companies for the period of 2012-2016. The method of data analysis used multiple linear regression. The result of this research showed that Corporate Social Responsibility is not a significant effect and have a positive relationship towards the earnings management.